Letter : Mattresses for your hospital in Spain - Pyke, Geoffrey
036-0022-001 VOLUNTARY INDUSTRIAL AID FOR SPAIN TELEPHONE: HOLBORN 6119 32 GREAT ORMOND STREET LONDON, W.C.1 6th June 1937 ADVISORY COMMITTEE: HARRY ADAMS, Chairman (Amalgamated Union of Building Trade Workers) ALFRED BARNES, M.P. (Chairman of the Co-operative Party) A.C BASSEBE (Hydraulic Coupling Co., Ltd.) H.G. BROTHERTON (Sheet Metal Workers Union) A.W. COSTER Electrical Trades Union) J. DUNNAGE. A.M. Inst., T. J. DAGGER (Amalgamated Society of Woodcutting Machinists) R.H. EDWARDS (National Union of Vehicle Builders) LORD FARINGDON BERT JOY (Amalgamated Society of Woodworkers) GEOFFREY PYKE, Hon. Secretary J. REEVES (Royal Arsenal Co-operative Society) JOE SCOTT, Treasurer (Amalgamated Engineering Union) J.R. SHANLEY (Amalgamated Union of Upholsterers) JACK TANNER (Amalgamated Engineering Union) Councillor D.C. WEBSTER, L.C.C. (National Union of Vehicle Builders) A.M. WALL (London Trades Council) Sir Walter Citrine, T.U.C., Smith Square, S.W.1. Dear Sir Walter, Mattresses for your hospital in Spain The cost of freight per fifty mattresses to Valencia would come to 36.2.6., i.e. about 14/6 per mattress. This, I fear, may make it uneconomical to supply mattresses in this way. Perhaps you would find what the hospital is paying for them locally. Of course, these mattresses would be of the very best quality. In any case, perhaps the most suitable way of getting them there would be to get one of the organisations which is sending out vehicles to take a load. An average-size lorry would take about fifty. Yours sincerely, Geoffrey Pyke Hon. Sec 292/946/36/22